Prevalence of Coronary Artery Disease at National Institute of Cardiovascular Disease Hyderabad (NICVD) Sindh - Mushahid Malik, Jawad Ahmad Khan, Ashok Kumar, Hanozia Hassan, Shakil Ahmed, Waheed Ali Panhwar, Wali Muhammad Mangrio, Yasir Akbar Jamali (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the prevalence of coronary artery disease at the NICVD Hospital, Hyderabad. Methods: At the National Institute of Cardiovascular Disease, a teaching hospital in Hyderabad, cross-sectional descriptive research was carried out. Total 130 patients were participated in study and all individuals were adults (18-60 years old) who presented at the general checkup clinic with a history or signs of CAD. A self-administered questionnaire designed for the study. Results: Among 130 patients, the proportions of significant risk factors for CAD were: 70% Hypertension, 36.2% Obesity, 36.2% Family history, and 36.9% diabetes mellitus. Signs and symptoms of the patients were Heart attacks 31.5%, heartburn 68.5%, AOT 36.9%, Chest pain 48.5%, and vomiting 7.7%. 80.8% of patients took chest pain tablets under the tongue. Patients currently smoking was 16.2%. Practical implication:- This study will prove very helpful for physician in managenment of coronary artery disease. Conclusion: Diabetes, hypertension, and high cholesterol are all modifiable risk factors that must be appropriately controlled. The community should place a high value on screening programs that may identify diseases before they develop and on adopting healthy habits. Keywords: Coronary artery Disease, Heart disease, NICVD